PENGEMBANGAN LKS MENGGUNAKAN MODEL PROBLEM CREATING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII SMP - Muliana Sari; Susiswo Susiswo; Toto Nusantara (Graduate School of Universitas Negeri Malang, 2017)
The aim of this research is developing student activity sheets (LKS) with model problem creating to improve students’ ability to think critically. This research is a developmental research with Plomp’s development model. This development model consists of three stages that are (1) preliminary research; (2) prototype phase; (3) assessment phase. The test subjects involved 27 students of class VIII of SMPN 1 Gambut. Based on the results of research from the design of LKS consists of cover, time allocation, learning objectives, content of LKS and assessment. Activities in the LKS consists of five stages of model problem creating that are learning objectives, problem context, create the problem, anticipate students’ solutions and reflect. The contents of the LKS consists questions that guide students to find mathematical concepts or principles, issues that need to be spent students and guide students to critical thinking that are basic clarification, basic for decision, inference and advanced clarification. The validations results from three validators showed that the LKS satisfied valid criteria. As a result on field testing in SMPN 1 Gambut students’ responses were positive. In addition, this learning instrument can increase students’ ability to think critically by 74%.Penelitian ini bertujuan untuk mengembangkan LKS dengan model problem creating yang dapat meningkatkan kemampuan berpikir kritis. Penelitian ini termasuk pengembangan dengan model pengembangan Plomp, yaitu (1) preliminary research (penelitian awal); (2) prototyping phase (fase pengembangan); (3) assessment phase (fase penilaian). Subjek uji coba melibatkan 27 siswa kelas VIII SMPN 1 Gambut. Desain LKS terdiri atas cover, alokasi waktu, tujuan pembelajaran, isi LKS, dan penilaian. Kegiatan dalam LKS terdiri atas lima tahapan model problem creating, yaitu menyampaikan tujuan pembelajaran, konteks masalah, menciptakan masalah, antisipasi jawaban, dan refleksi. Isi LKS terdiri dari pertanyaan-pertanyaan yang menuntun siswa menemukan konsep atau prinsip matematika, masalah yang perlu diselesaikan siswa, dan memandu siswa untuk berpikir kritis antara lain memberikan penjelasan dasar, membangun keterampilan dasar, menyimpulkan dan memberikan penjelasan lanjut. Hasil validasi LKS dari tiga validator menunjukkan bahwa LKS memenuhi kriteria valid. Berdasarkan uji coba lapangan di SMPN 1 Gambut respon siswa terhadap LKS positif. Selain itu, peningkatan kemampuan berpikir kritis siswa sebesar 74%.